Linguistic Analysis of Northern Irish Court Judgments (2014-2020) - Tena, Francisco Godoy (New Horizons in Education and Social Studies Vol. 9, 2021)
Court Judgments are essential court documents in legal systems. Following a previous study [1], the aim of this research follows an extended study of court documents (judgments) from Northern Ireland issued between 2014 and 2020. The methodology used to analyse these court judgments is based on van Dijk’s macrostructural analysis. Thanks to this study, we will summarise the most remarkable semantic features that structure internally a recent corpus of 40 digital court judgments from Northern Ireland in order to simplify them for experts from diverse academic fields.